A rare heterozygous SP7 variant c.1019A>c (p.Glu340Ala) in a Malaysian family with Osteogenesis Imperfecta Type XII: a case report - Teh, Hui Wen; Lee, Yee Lin; Musa, Nurul Huda; Thilakavathy, Karuppiah (Universitas Gadjah Mada, 2024)
Osteogenesis imperfecta (OI) is a rare genetic disorder characterized by increased bone fragility, low bone density, and frequent fractures. Although most cases are associated with mutations in collagen genes (COL1A1 and COL1A2), non-collagen gene mutations, such as those in SP7, have been linked to OI type XII. Here, we report on a Malaysian family affected by a rare SP7 variant.